Verbing and Linguistic Innovation - Michaelis, Laura A.; Hsiao, Allen Minchun (Frontiers in Communication, 2021)
Denominal verbs are produced by a syntactic category shift, conversion, in which the word’s inflectional and combinatory potential change while its internal composition does not (Valera 2015: 322). Perhaps no language owes as many of its verbs to the conversion strategy as English (Koutsoukos 2020), the majority being denominal (noun-derived) verbs, e.g., Widespread seedless cultivars typically fruit twice yearly in the Caribbean. Language users rely on certain inferential strategies to figure out what novel denominal verbs mean, combining information from multiple sources, including salient properties of the source noun’s denotatum, the event structure of the clause in which that noun serves as a predicator, and socio-cultural knowledge. How exactly does this work? Our answer recalls lessons of Clark & Clark 1979: denominal verbs have context-dependent rather than fixed meanings, and interpretations that rely on cooperation between speaker and hearer. These are lessons seemingly forgotten by influential derivation-based accounts, which leverage the formal similarity between denominal verbs and noun-incorporating verbs like backstab and manspread. While, as discussed here, syntacticized approaches to semantic representation fail to account for the interpretive latitude that denominal verbs display, there are reasons to reject a strong view of context dependence as well. For Clark and Clark, interpretations of innovative denominal verbs either directly reflect criterial features of their source nouns or are ad hoc, derived from “moment-to-moment cooperation,” including gestures, allusions, and “other momentarily relevant facts about the conversation” (1979: 783). We argue that denominal interpretations are more tightly regulated, and involve reconciling results of four distinct interpretive strategies: nominal frame computation (Fillmore 2006), verb-construction integration (Goldberg 2005, Michaelis 2004), co-composition (Pustejovsky 1998, 2012), and conceptual blending (Fauconnier & Turner 2004). In line with Clark & Clark’s (1979) convention for the interpretation of innovative denominal verbs, we argue that nouns used in innovative denominal formations are chosen based on relational properties of entities denoted by those nouns (e.g., behavior, composition, use, provenance). At the same time, our account leaves fewer interpretive factors to vagaries of context.